Human Uterine Biopsy: Research Value and Common Pitfalls - Maclean, Alison; Kamal, Areege; Adishesh, Meera; Alnafakh, Rafah; Tempest, Nicola; Hapangama, Dharani K. (International Journal of Reproductive Medicine, 2020)
The human uterus consists of the inner endometrium, the myometrium, and the outer serosa. Knowledge of the function of the uterus in health and disease is relevant to reproduction, fertility, embryology, gynaecology, endocrinology, and oncology. Research performed on uterine biopsies is essential to further the current understanding of human uterine biology. This brief review explores the value of the uterine biopsy in gynaecological and human fertility research and explores the common problems encountered when analysing data generated from different types of uterine biopsies, with the aim of improving the quality, reproducibility, and clinical translatability of future research.